Allelic Variants for Candidate Nitrogen Fixation Genes Revealed by Sequencing in Red Clover (Trifolium pratense L.) - Trněný, Oldřich; Vlk, David; Macková, Eliška; Matoušková, Michaela; Řepková, Jana; Nedělník, Jan; Hofbauer, Jan; Vejražka, Karel; Jakešová, Hana; Jansa, Jan; Piálek, Lubomír; Knotová, Daniela (International journal of molecular sciences, 2019)
Plant-rhizobia symbiosis can activate key genes involved in regulating nodulation associated with biological nitrogen fixation (BNF). Although the general molecular basis of the BNF process is frequently studied, little is known about its intraspecific variability and the characteristics of its allelic variants. This study's main goals were to describe phenotypic and genotypic variation in the context of nitrogen fixation in red clover (Trifolium pretense L.) and identify variants in BNF candidate genes associated with BNF efficiency. Acetylene reduction assay validation was the criterion for selecting individual plants with particular BNF rates. Sequences in 86 key candidate genes were obtained by hybridization-based sequence capture target enrichment of plants with alternative phenotypes for nitrogen fixation. Two genes associated with BNF were identified: ethylene response factor required for nodule differentiation (EFD) and molybdate transporter 1 (MOT1). In addition, whole-genome population genotyping by double-digest restriction-site-associated sequencing (ddRADseq) was performed, and BNF was evaluated by the natural 15N abundance method. Polymorphisms associated with BNF and reflecting phenotype variability were identified. The genetic structure of plant accessions was not linked to BNF rate of measured plants. Knowledge of the genetic variation within BNF candidate genes and the characteristics of genetic variants will be beneficial in molecular diagnostics and breeding of red clover.
Keywords: Host Microbial Interactions; biological nitrogen fixation; polymorfismus genetický; symbióza; fenotyp; red clover; kořeny rostlin; Phenotype; Polymorphism, Genetic; Genotype; Rhizobium; Symbiosis; interakce mikroorganismu a hostitele; Sequence Analysis, DNA; associated genes; Nitrogen Fixation; sekvenční analýza DNA; associated polymorphisms; genome-wide association; fixace dusíku; Alleles; genotyp; Plant Roots; alely; rostlinné geny; Trifolium; Genes, Plant